Distribution and Incidence Leaf Diseases of Banana in Several Banana Production Centers in North Sumatra, West Sumatra Bengkulu and West Java - Sahlan, Sahlan; Soemargono, A. (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2011)
The research was aimed to determine the type, the distribution and the incidence of banana leaf diseases in several production centers in West Sumatra, Bengkulu, North Sumatra and West Java. Direct observations on banana orchards were conducted in some districts in Simalungun, Deli Serdang and Medan (North Sumatra), Tanah Datar, Limapuluh Kota, Agam, Pariaman and Pasaman (West Sumatra), Rejang Lebong and Kepahyang (Bengkulu), Sukabumi, Purwakarta and Subang (West Java) from November to December 2006. Two banana orchards were randomly selected in each district. Plant population at the selected orchard was at least 100 plants. From each sampled orchard, if banana population consisted of similar or only one variety, 10 plants were randomly chosen according to wind direction. Meanwhile, when the banana varieties were varied, five plants were randomly selected. The result showed that Black Sigatoka and Eumusae leaf spot were found in West Sumatra, Bengkulu and North Sumatra at severity level of between 15 % to 62.31%, whilst speckle disease was mainly found in North Sumatra and in parts of West Sumatra at severity level of between 72,72% to 100% and 15 to 30%, respectively. Banana varieties that were primarily attacked by leaf diseases were Cavendish, Telor, Barangan and Emas.Keywords : bananas, black sigatoka, Eumusae, speckle, disease incidence and distribution